National or Local? The Demand for News in Italy during Covid-19 - Stefano Castriota; Marco Delmastro; Mirco Tonin (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Looking at TV news viewership in Italy during the COVID-19 pandemic using actual consumption data, we investigate whether demand for national and local news depends on national or local epidemiological developments, as measured by the number of new positives or the number of currently positives in any given day. Exploiting the fact that the seriousness of the pandemic displays a great deal of variation among the different regions, we find that at the regional level demand for both national news and, more surprisingly, local news responds to the national epidemiological developments rather than to the local ones. This has implications for the incentives faced by local politicians to take preventive action.
Keywords: D12; L82; 330; news; local news; TV; Covid-19